Slavoj iek tentang Manusia sebagai Subjek Dialektis - Reza A.A Wattimena (Jurnal Orientasi Baru, 2011)
What or who is human? This is one of the oldest questions in history. Philosopherand scientist from various disciplines try to answer it based on their researchand theories. What is unique in iek approach is his effort to combine twodifferent schools of thought as an intellectual instrument to answer this question,namely German Idealism and Jacques Lacans Psychoanalysis. Inspired by thephilosophy of German Idealism, he argued that the essence of human is notinside his or her self, but outside, namely the symbolic order that determine theirself. And inspired by Lacan, he argued that the self always embedded in thesymbolic order, and constantly disrupted by the Real. In this context, we can saythat human is a dialectical subject.